Exhaled breath measures of inflammation: are they useful in neonatal chronic lung disease?. Issue 1 (21st December 2004) - Harrison, C M; Andersen, C C
Abstract : Neonatal chronic lung disease is a common problem for surviving infants of extreme prematurity. Although the precise pathophysiology is still not known, it is clear that inflammation provides a common link that amplifies the injury to the premature lung. Current invasive measures of pulmonary inflammation include markers in blood and airway effluent, with the cellular composition of tracheal fluid being the "gold standard". In this article available exhaled breath measures, particularly nitric oxide, carbon monoxide, volatile hydrocarbons, and exhaled breath condensate, are reviewed with particular reference to sample collection, analysis, and common pitfalls as they apply to the ventilated premature newborn at risk of chronic lung disease. Although they have great potential, all measures require thorough validation before being used clinically.